Pengaruh Pelatihan dan Kompetensi Profesional terhadap Kinerja Guru di SD Negeri sekecamatan Kertapati Palembang - Meri Hartati; Dessy Wardiah; Andi Rahman (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to analyze the influence of training and professional competence on the performance of public elementary school teachers in the Kertapati District, Palembang. Training is considered a crucial factor in improving human resource quality, especially teachers, which directly contributes to enhancing the quality of education in elementary schools. Professional competence includes the knowledge, skills, and attitudes required for teachers to perform their duties effectively and efficiently. The research method used is quantitative with a survey approach. The sample consists of public elementary school teachers in Kertapati District selected by purposive sampling. Data were collected using a questionnaire tested for validity and reliability, then analyzed using multiple linear regression techniques. The results show that training and professional competence simultaneously have a positive and significant effect on teacher performance. Partially, training contributes to improving teaching ability, while professional competence enhances task execution and interaction with students. The implication of this study is the importance of increasing the quantity and quality of training and developing teachers' professional competence as efforts to improve teacher performance, which ultimately impacts the quality of elementary education in Kertapati District, Palembang.